Mental health research priorities in Australia: a consumer and carer agenda - Banfield, Michelle A. (Health Res Policy Syst, 2018)
BACKGROUND: The perspectives of mental health consumers and carers are increasingly recognised as important to the development and conduct of research. However, research directions are still most commonly developed without consumer and carer input. This project aimed to establish priorities for mental health research driven by the views of consumers and carers in Australia. METHOD: The project was conducted in two studies. Firstly, a face-to-face discussion forum held in the Australian Capital Territory (Study 1; n = 25), followed by a national online survey (Study 2; n = 70). Participants in both studies were members of the community who identified as a mental health consumer, carer or both. In Study 1, participants developed topics for mental health research in small group discussions, then voted on which topics, developed across all groups and sorted into thematic areas, were a priority. An online survey was developed from these research topics. Study 2 participants were asked to rate topics on a 5-point priority scale and rank the relative importance of the highest-rated topics. RESULTS: At the forum, 79 topics were generated and grouped into 14 thematic areas. Votes on priorities were spread across a large number of topics, with the greatest overall support for research relating to integrating care that is sensitive to past experiences of trauma into mental health service delivery (trauma-informed care). Survey responses were similarly spread, with the majority of research topics rated as important by at least 50% of participants and no clear individual priorities for research identified. Amongst items rated as important by approximately 80% of participants, key research areas included the delivery of services, and consumer and carer involvement. CONCLUSIONS: Australian mental health consumers and carers demonstrate a strong understanding of the mental health system and its inadequacies. Although clear specific priorities are difficult to establish, consistent areas of focus are services and the role consumers and carers can play in their improvement. However, for consumer and carer views to be at the forefront of research, it is important to regularly update research agendas and work in partnership across the whole research process. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12961-018-0395-9) contains supplementary material, which is available to authorized users.